PATIENT PRECEPTION REGARDING CROSS INFECTION CONTROL; A CROSS SECTIONAL STUDY - Nousheen Khan; Rafia Sartaj; Sharina Naz; Mustafa Sajid; Muhammad Jamil; Mohsin Javaid (Pakistan Oral & Dental Journal, 2021)
Patients should also know about cross infection control along with the healthcare workers. Media coverage has done a good job to raise the knowledge of the patients about cross infection control specially gloves and face mask. Objective of the study is to perceive the knowledge of the patients regarding the use of gloves, masks, eye wear and method of sterilization. Study design was cross sectional survey. A questionnaire was distributed among three hundred and fifty individuals who were selected randomly. 332 patients were responded among three hundred and fifty. Out of 332 patients 205 were males and 127 were females. Most of the patients (248) had second visit in dental clinics. 98% patients agreed that dentist must used gloves during dental treatment but only 24% patients knew about autoclave. Conclusion of the study is that patients are often well aware about basics of barrier technique but are deficient in knowledge of methods of sterilization.